RETRACTED: Senior citizens’ ecological and digital literacy in E-Airticket reservation in the era of the internet of things (IoT) - Charernnit Kanittha; Komolvanij Theppaluk; Treruttanaset Pongsapak; Kuosuwan Bavornluck (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001